Narrative Medicine: Principles, Benefits and Challenges - Cunegundes, Kelly Simone (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
Narratives are a fundamental part of human lived experiences and disclose values, meanings, and purposes. Narrative Medicine emerged from the urgent call to react to the radicalization of biomedical model in healthcare, that promoted significant advances in medicine but, at the same time, moved away subjectivity from medical-patient relationship. Narrative competence is understood as the capability to listen, absorb, interpret, and take decisions based on patients’ accounts and that competence involves textual, creative, and affective abilities when listening or reading stories. The goal of this article is to discuss the history, principles, practice, and challenges of narrative medicine.